EFFECT OF FORMALDEHYDE-PROTECTED DIETS ON MILK YIELD, COMPOSITION AND SOME BLOOD BIOCHEMICAL PARAMETERS IN KARADI EWES - Mustafa, K. N. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
An experiment was conducted to study the effect of feeding formaldehyde-treated diets on milk yield, composition and some blood biochemical parameters of Karadi ewes in mid lactating period. Nine lactating Karadi ewes in their second lactation and weighing 43.42 ± 0.4 kg were used in this study. Following one-week adaptation period, the ewes were allocated into 3x3 Latin-square and fed three different diets, the 1st untreated basal diet (T1), the 2nd barley 75%, wheat bran 7% and soybean meal 10% treated with formaldehyde 9l/ton (T2) and 3rd group wheat bran7% and soybean meal 20% treated with formaldehyde (T3). The ewes were offered 1.750 kg/ewe of concentrate in addition to grazing for 5-6 hr per day. Results showed that the ewes fed T2 and T3 diets had a higher (P<0.05) daily milk yield as well as milk fat, protein and lactose yield than ewes fed control diet. Blood urea concentration was higher (P<0.05), but albumin, triglyceride and glucose was lesser (P<0.05) in ewes given T2 and T3 diets than those fed T1 diet. It can be concluded that feeding Karadi ewes formaldehyde-treated diet improved milk yield and increased milk’s total solids.